TAXONOMY OF BLENDED LEARNING AND ITS APPLICATION IN THE NEW NORMAL ERA - Nur Ismiyati (International Conference on Social and Islamic Studies, 2021)
The application of information technology in education has the undoubted potential to upsurge the quality of teaching and dexterity in learning. The Covid-19 pandemic that occurred in the world, especially in Indonesia, caused problems, especially in the education sector. The education crisis caused by the Covid-19 pandemic has caused problems that are not separated from the growth of the digitalization revolution in education. So, it is necessary to learn by using services the help of electronic devices called e-learning. One of the e-learning model that can be used in online learning is blended learning. Blended learning as a formal education program that has moments in which the student studies the content through online resources and moments when teaching is supervised in the classroom. This paper is literature review and investigations in the taxonomy of blended learning as follows: (1) specifically categorization is based on transmission mode that describe challenges linked to blended learning are culture and blended learning environment, finding the right design, demand on time, well integrated teamwork, communication; (2) learning syles from four models of blended learning namely Rotation model, Flex model, A La Carte model, and Enriched Virtual model; (3) blended learning based on web-support such as linking-the lecturer curates, wrapping-the lecturer guides, wisc-online, khan academy, VLE/LMS, PLE, personal learning networks, mashups, mupples.